2019
DOI: 10.1002/navi.277
|View full text |Cite
|
Sign up to set email alerts
|

Improved Time of Arrival measurement model for non‐convex optimization

Abstract: The quadratic system provided by the Time of Arrival technique can be solved analytically or by nonlinear least squares minimization. An important problem in quadratic optimization is the possible convergence to a local minimum, instead of the global minimum. This problem does not occur for Global Navigation Satellite Systems (GNSS), due to the known satellite positions. In applications with unknown positions of the reference stations, such as indoor localization with self-calibration, local minima are an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In [20] we have proven that the improved objective function two F 2 has a saddle point at the local minimum of objective function two F 2 . In test scenraios with no or small noise the improved objective function onw F L1 never converges into a local minimum.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In [20] we have proven that the improved objective function two F 2 has a saddle point at the local minimum of objective function two F 2 . In test scenraios with no or small noise the improved objective function onw F L1 never converges into a local minimum.…”
Section: Discussionmentioning
confidence: 86%
“…The final proof of the hypothesis was provided with the help of the Cauchy-Bunyakovsky-Schwarz inequality [7]. Alternatively, the equation 29 in [20] can also be obtained from the variance V ar(…”
Section: Reason For the Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In [17], we demonstrated that if the base station positions are known and only the tag positions have to be estimated, an additional dimension in the l 2 norm of the TOA objective function transforms the local minimum to a saddle point. This fact has been proven analytically for the squared objective function and empirically for the general TOA objective function through more than 10,000 test scenarios with different constellations and initial estimates.…”
Section: Tdoa Localizationmentioning
confidence: 99%